2008
DOI: 10.1149/1.2885101
|View full text |Cite
|
Sign up to set email alerts
|

Deposition of Ultrathin Nafion Layers on Sol–Gel-Derived Phenylsilsesquioxane Particles via Layer-by-Layer Assembly

Abstract: Ultrathin layers of oppositely charged poly͑diallyldimethylammonium chloride͒ ͑PDDA͒ and Nafion were alternately deposited on negatively charged phenylsilsesquioxane ͑PhSiO 3/2 ͒ microparticles via layer-by-layer assembly. An extremely small amount of Nafion was used for the layers. The average thickness of a Nafion layer was estimated to be 2.6 nm from the amount of deposited Nafion and the density. A monolithic sheet was obtained from PhSiO 3/2 particles with PDDA and the Nafion multilayer when the particles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 22 publications
(22 reference statements)
0
18
0
Order By: Relevance
“…Compared with the traditional Langmuir-Blodgett thin-film deposition method, the ease of film formation and film stability and versatility are the main advantages of this new technique [1]. Based on the combination of various polyelectrolyte pairs and substrates, the LBL assembled membranes have been studied for a wide range of applications such as pervaporation [2,3], fuel cell [4], nanofiltration (NF) [5,6] and wastewater treatment [7].…”
Section: Introductionmentioning
confidence: 99%
“…Compared with the traditional Langmuir-Blodgett thin-film deposition method, the ease of film formation and film stability and versatility are the main advantages of this new technique [1]. Based on the combination of various polyelectrolyte pairs and substrates, the LBL assembled membranes have been studied for a wide range of applications such as pervaporation [2,3], fuel cell [4], nanofiltration (NF) [5,6] and wastewater treatment [7].…”
Section: Introductionmentioning
confidence: 99%
“…(H 3 PW 12 O 40 :WPA) [189] and the other is composed of PDDA and Nafion [190]. Their results showed that the proton conductivities of particles coated by WPA/PDDA and Nafion/PDDA multilayered PEC membranes were about 10 −4 and 10 −5 S cm −1 , which were 4 orders of magnitude higher than those of pristine phenylsilsesquioxane particles.…”
Section: Multilayered Pec Membranes For Pemfcmentioning
confidence: 99%
“…It has been reported that the chemical, thermal, and mechanical stabilities of membranes can be improved by dispersing an inorganic filler in the organic matrix. It has also been reported that rapid ionic transfer through the interface between the two different materials occurs in some proton-conducting organic/inorganic composite materials [12,15]. Higher stabilities, greater proton conductivity, or better fuel-cell performance have been reported for some composite systems such as Nafion/TiO 2 , SPEEK/WO 3 , SPES/ heteropoly acid (H 3 PW 12 O 40 ), SPES/boron phosphate (BPO 4 ), or SPEEK/ organically treated montmorillonite (OMMT) [12][13][14][16][17][18][19].…”
Section: Introductionmentioning
confidence: 97%